The Influence of Managerial Orientation in Decision-Making Processes - Rusdianto Rusdianto (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This research aims to examine managerial preferences in the resource allocation process. This research used an experimental method to test whether resource availability, stakeholder claims, and managers’ affiliations to stockholders can influence the decision-making process of resource allocation. The results show that resource availability, stakeholder claims, and managers’ affiliation could influence the resource allocation process. The results of the research contribute to several things. The first is to show that stakeholder theory can test managerial preferences at the individual level. Secondly, the resources distribution is influenced by behavioral factors associated with normative stakeholder theory.